AF291 and AE391 antibodies recognize a Dictyostelium HA-tagged protein by Western blot - Jauslin, Tania (Antibody Reports, 2019)
The AF291 and AE391 antibodies detect an HA-tagged Dictyostelium discoideum protein by Western blot.